2020
DOI: 10.1136/bmjopen-2019-035361
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review protocol examining the influence of surgeon personality on perioperative decision making in abdominal surgery

Abstract: IntroductionThere is limited published literature exploring how the personality traits of surgeons may influence preoperative decision making, particularly in the context of visceral/abdominal surgery. Multiple validated personality scoring systems exist and have been used to describe surgeon personalities previously. The degree to which each trait is expressed by abdominal surgeons is neither currently known, nor the impact of these traits on postoperative outcomes. The protocol has been written in line with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…Our systematic review was first registered on PROSPERO (University of York, UK) in September 2019 (CRD42019151375), and the full protocol published in February 2020 (PMID 32019819) [ 21 ]. No deviations from the protocol occurred.…”
Section: Methodsmentioning
confidence: 99%
“…Our systematic review was first registered on PROSPERO (University of York, UK) in September 2019 (CRD42019151375), and the full protocol published in February 2020 (PMID 32019819) [ 21 ]. No deviations from the protocol occurred.…”
Section: Methodsmentioning
confidence: 99%
“…Surgical personality is hypothesized to affect a patient's mortality and morbidity. [ 6 ] It is believed that low scores in openness and emotional stability may influence decision making in surgery and might affect the morbidity and mortality rate of patients. [ 6 ] A study, done in Ohio, with a sample size of 192 medical staff found that surgeons scored significantly higher on conscientiousness and extraversion but lower on agreeableness compared to nonsurgeons.…”
mentioning
confidence: 99%
“…This has the potential to delay the diagnosis of a leak and its subsequent management, and to an increase in morbidity. However, research into surgical personality types and human factors has become a key focus in patient safety and assessment of Non-Operative Technical Skills for Surgeons (NOTSS) are increasingly integrated into surgical teaching programmes[68][69][70]. These include cognitive and interpersonal skills with the aim of improving situational awareness and decision making, in an attempt to reduce adverse surgical events.…”
mentioning
confidence: 99%